AN ANALYSIS ON STUDENTS’ INTRINSIC MOTIVATION IN LEARNING ENGLISH - Merdekawati, Restu; Sada, Clarry; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is based on the problem of Students? Intrinsic Motivation In Learning English in the Eleventh Grade Students of Accounting Study Program At SMK Negeri 1 Pontianak. The main objective of this research is answering the research problems; how high is the students? instrinsic motivation in learning English and the factors that influence the students? instrinsic motivation in learning English. The purpose of this research is to find the students? instrictic motivation in learning English based on Self-Determination Theory (SDT). The writer applied questionnaire and interview in this research. The conclusion for autonomy factor was most of the students were experiencing behaviour that emanate from themselves rather than from external sources and accompanied by feeling of curiosity and interest in learning English. Students are autonomous when they willingly devote their time and energy in learning English as shown in their answers from the questionnaire given to them. The conclusion for competence factor was most of the students can be said to be competent when they feel able to meet the challenges in their English learning as shown in their answers from the questionnaire given to them. The conclusion for relatedness factor was most of the students feels the psychological sense of being with others, whether they are fellow students or teachers in learning activity. Keywords: Intrinsic Motivation, Self-Determination Theory, learning English